Study And Analysis of Green Concrete by Using Industrial Waste Materials as Sustainable Construction - Udayasree, Bakigari; Kumar, G. Shravan (International Journal of Membrane Science and Technology, 2023)
Presently, the problem is to transition to a new form that can sustain the natural system. This demand a new ideas of the community’s methods for providing construction and infrastructure. Perhaps there is a need for a concerted effort to develop innovative and alternative novel construction materials. Industrial waste such as marble powder, quarry dust, and fly ash, among others, are used to reduce consumption of natural resources and energy as well as environmental pollution. By reusing industrial waste, we are able to reduce environmental impact and industrial waste disposal issues.in this analysis 7-day, 14-day, and 28-day compressive and split tensile tests were performed on the concrete mixtures that were then compared. In M25 concrete mix, 50% of the cement was substituted with fly ash, and the sand was completely replaced with 50% quarry dust and 50% marble powder. Cement is reduced by 15% to 25% when such waste is utilized. Green concrete is an efficient method for reducing environmental contamination and enhancing the extreme durability of concrete. This trend will remain during all stages of the construct-ability and rehabilitation of infrastructure. The versatility of green concrete and its performance derivatives will satisfy many future requirements.